Golf ball material and golf ball

JP7632023B2Active Publication Date: 2025-02-19BRIDGESTONE SPORTS CO LTD
View PDF -1 Cites 0 Cited by

Patent Information

Application Number
JP2021070462
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-19
Publication Date
2025-02-19
Estimated Expiration
2041-04-19

Smart Images

  • Figure 0007632023000005
    Figure 0007632023000005
  • Figure 0007632023000006
    Figure 0007632023000006
  • Figure 0007632023000001
    Figure 0007632023000001
Patent Text Reader

Abstract

SOLUTION: To provide a golf ball material including: (I) a multi-component copolymer which includes, a conjugated diene unit, a non-conjugated olefin unit, and an aromatic vinyl unit; (II) a binary copolymer of olefin and α,β-unsaturated carboxylic acid having C3-C8, and / or a ternary copolymer of olefin and α,β-unsaturated carboxylic acid having C3-C8 and α,β-unsaturated carboxylic acid ester thereof, or a metal neutralized product thereof, in which the conjugated diene unit includes a butadiene unit, the non-conjugated olefin unit includes a unit selected from an ethylene unit, a propylene unit, and 1-butene unit, the aromatic vinyl unit includes a styrene unit, and a content of the conjugated diene unit to the multi component copolymer is 5 mass% or greater.EFFECT: A golf ball material is soft and is excellent in rebound resistance, and a golf ball using the material as a cover provides dominance in competition to a golfer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a golf ball material and a golf ball using the same, and in particular to a golf ball material that is suitable for use as a material for each layer (intermediate layer or outermost layer) of a golf ball having one or more cover layers that encase a core, and a golf ball using the same. [Background technology]

[0002] In order to realize a golf ball that combines a soft feeling with high resilience, it has been proposed to add a hydrogenated aromatic vinyl elastomer such as styrene-ethylene-butylene-styrene block copolymer (SEBS) to an ionomer resin. For example, JP-A No. 2001-95948 (Patent Document 1) and JP-A No. 2001-32763 (Patent Document 2) propose a resin composition in which a thermoplastic elastomer such as SEBS and a tackifier are blended with an ionomer resin.

[0003] However, although adding SEBS to an ionomer resin can impart a soft feeling, adding too much SEBS has the adverse effect of reducing the resilience.

[0004] In addition, materials that completely neutralize the acid in an ionomer resin composition by adding a fatty acid to the ionomer resin composition have been proposed as golf ball materials. For example, JP-A-2001-120686 (Patent Document 3) and JP-A-2001-348467 (Patent Document 4) propose highly neutralized ionomer resin materials in which a fatty acid and a basic inorganic metal compound are blended with an ionomer resin composition.

[0005] However, although the highly neutralized ionomer resin material exhibits high resilience, it cannot be said that it provides sufficient softness. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2001-95948 A [Patent Document 2] JP 2001-32763 A [Patent Document 3] JP 2001-120686 A [Patent Document 4] JP 2001-348467 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a golf ball material and a golf ball which are soft and have excellent resilience. [Means for solving the problem]

[0008] As a result of intensive research into achieving the above-mentioned object, the present inventors have found that a golf ball material is a multicomponent copolymer having conjugated diene units, non-conjugated olefin units, and aromatic vinyl units, using an acid-containing copolymer containing an olefin such as an ionomer resin and an α,β-unsaturated carboxylic acid and a metal salt thereof as a base resin, wherein the conjugated diene units include butadiene units, the non-conjugated olefin units include units selected from the group consisting of ethylene units, propylene units, and 1-butene units, and the aromatic vinyl units include styrene units, and the content of the conjugated diene units in the multicomponent copolymer is 5% by mass or more, thereby making it possible to maintain unexpectedly high rebound resilience even with a low hardness. In other words, when a golf ball is constructed using this material for a cover, a golf ball is provided which is excellent in rebound resilience and provides high flight performance while providing a sufficient soft feel. This finding led to the completion of the present invention.

[0009] Accordingly, the present invention provides the following golf ball material and golf ball. 1. The following components (I) and (II) (I) a multicomponent copolymer having a conjugated diene unit, a non-conjugated olefin unit, and an aromatic vinyl unit; and (II) A binary copolymer of an olefin and an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms, and / or a ternary copolymer of an olefin and an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms and its α,β-unsaturated carboxylic acid ester, or a metal-neutralized product thereof The conjugated diene unit comprises a butadiene unit, the non-conjugated olefin unit comprises a unit selected from the group consisting of an ethylene unit, a propylene unit and a 1-butene unit, the aromatic vinyl unit comprises a styrene unit, and the content of the conjugated diene unit in the multicomponent copolymer is 10~80% by mass 1. A golf ball material comprising: 2 The content of the non-conjugated olefin unit in the multi-component copolymer which is the component (I) is 20~90% by mass The above is 1 The golf ball material described herein. 3 The content of the aromatic vinyl unit in the multi-component copolymer which is the component (I) is 3~30% by mass The above is 1 or 2 The golf ball material described herein. 4 The non-conjugated olefin unit is an ethylene unit. 3 2. The golf ball material according to claim 1 , 5 The multi-component copolymer of component (I) is a copolymer polymerized by a gadolinium metallocene complex catalyst. 4 2. The golf ball material according to claim 1 , 6 The content of the component (II) relative to the total amount of the components (I) and (II) is 5 to 95 mass%. 5 2. The golf ball material according to claim 1 , 7 .The above 1~ 6 2. The golf ball material according to claim 1 , 8 The above-mentioned 1 to 5 are used as a cover material for golf balls.7 2. The golf ball material according to claim 1 , 9 A golf ball having a core made of one or more layers and a cover made of one or more layers covering the core, wherein at least one layer of the cover is 8 2. A golf ball formed from the golf ball material according to claim 1. Effect of the Invention

[0010] The golf ball material of the present invention is soft and has excellent resilience, and a golf ball using the golf ball material of the present invention for its cover provides a competitive advantage to golfers. [Brief description of the drawings]

[0011] [Figure 1] 2 is a graph showing the relationship between the material hardness and the rebound resilience of the covers in Examples 1 to 5 and Comparative Examples 1 to 5. [Diagram 2] 1 is a graph showing the relationship between the material hardness and the rebound resilience of the covers in Examples 6 and 7 and Comparative Examples 6-8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will now be described in further detail. The golf ball material of the present invention is characterized by containing the following components (I) and (II): (I) a multicomponent copolymer having a conjugated diene unit, a non-conjugated olefin unit, and an aromatic vinyl unit; and (II) A binary copolymer of an olefin and an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms, and / or a ternary copolymer of an olefin and an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms and its α,β-unsaturated carboxylic acid ester, or a metal-neutralized product thereof

[0013] Component (I) is a multicomponent copolymer having conjugated diene units, non-conjugated olefin units, and aromatic vinyl units. This multicomponent copolymer is the multicomponent copolymer described in Japanese Patent No. 6780827 and is described as follows:

[0014] <Conjugated diene unit> The multicomponent copolymer contains a conjugated diene unit. The conjugated diene unit is a structural unit derived from a conjugated diene compound as a monomer. The multicomponent copolymer can be polymerized using a conjugated diene compound as a monomer, and therefore has superior crosslinking properties compared to a copolymer polymerized using a non-conjugated diene compound such as a known EPDM. The conjugated diene compound contains a butadiene unit. The butadiene unit is a structural unit derived from a butadiene compound, and specific examples of the butadiene compound include 1,3-butadiene, isoprene, 1,3-pentadiene, and 2,3-dimethyl-1,3-butadiene. In addition, the conjugated diene unit in the multicomponent copolymer preferably contains a 1,3-butadiene unit, and more preferably consists of only a 1,3-butadiene unit.

[0015] In addition, the multicomponent copolymer preferably has a cis-1,4 bond content of 50% or more in the entire conjugated diene unit, more preferably 70% or more, even more preferably 80% or more, and particularly preferably 90% or more. Such a multicomponent copolymer having a high cis-1,4 bond content in the entire conjugated diene unit can be obtained by using a conjugated diene compound, a non-conjugated olefin compound, and an aromatic vinyl compound as monomers. On the other hand, the vinyl bond (1,2 vinyl bond, 3,4 vinyl bond, etc.) content in the entire conjugated diene unit is preferably 30% or less, more preferably 15% or less, even more preferably 10% or less, and particularly preferably 6% or less. In addition, the trans-1,4 bond content in the entire conjugated diene unit is preferably 30% or less, more preferably 15% or less, and even more preferably 10% or less. The contents of cis-1,4 bonds, trans-1,4 bonds and vinyl bonds can be determined from the integral ratios of the results of 1H-NMR and 13C-NMR measurements.

[0016] The conjugated diene compound may be used alone or in combination of two or more kinds. That is, the multicomponent copolymer may contain one type of conjugated diene unit alone or may contain two or more types. The content of the conjugated diene unit is preferably 10% by mass or more of the entire multicomponent copolymer, more preferably 15% by mass or more. The content of the conjugated diene unit is preferably 80% by mass or less of the entire multicomponent copolymer, more preferably 60% by mass or less, and even more preferably 50% by mass or less.

[0017] <Non-conjugated olefin unit> The multicomponent copolymer contains a non-conjugated olefin unit. The non-conjugated olefin unit is a structural unit derived from a non-conjugated olefin compound as a monomer. The non-conjugated olefin compound is selected from the group consisting of ethylene, propylene, and 1-butene. In particular, in order to impart sufficient impact resilience and softness to the golf ball material, it is preferable that the non-conjugated olefin unit is an ethylene unit.

[0018] The non-conjugated olefin compound may be used alone or in combination of two or more. That is, the multicomponent copolymer may contain one type of non-conjugated olefin unit alone or two or more types. The content of the non-conjugated olefin unit is preferably more than 20 mass% and less than 90 mass% of the entire multicomponent copolymer, more preferably 30 to 85 mass%, further preferably 40 to 80 mass%, and most preferably 45 to 75 mass%.

[0019] <Aromatic vinyl unit> The above multicomponent copolymer contains an aromatic vinyl unit. The aromatic vinyl unit is a constituent unit derived from an aromatic vinyl compound as a monomer. Examples of aromatic vinyl compounds include styrene compounds, specifically styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, o-ethylstyrene, m-ethylstyrene, p-ethylstyrene, etc. The aromatic vinyl unit in the above multicomponent copolymer contains a styrene unit, and more preferably consists of only a styrene unit. The aromatic ring in the aromatic vinyl unit is not included in the main chain of the copolymer unless it is bonded to an adjacent unit.

[0020] The aromatic vinyl compound may be used alone or in combination of two or more. That is, the multicomponent copolymer may contain one type of aromatic vinyl unit alone or two or more types. The content of the aromatic vinyl unit is 3 to 30% by mass of the entire multicomponent copolymer. If the content of the aromatic vinyl unit is less than 3% by mass or more than 30% by mass, the length of the non-conjugated olefin portion of the copolymer cannot be suppressed, and durability improvement derived from the non-conjugated olefin crystals cannot be achieved. The content of the aromatic vinyl unit is preferably 3 to 30% by mass of the entire multicomponent copolymer, more preferably 5 to 25% by mass, and even more preferably 10 to 20% by mass.

[0021] The number of types of monomers in the above-mentioned multicomponent copolymer is not particularly limited, as long as the multicomponent copolymer contains a conjugated diene unit, a non-conjugated olefin unit, and an aromatic vinyl unit. The multicomponent copolymer may have other structural units other than the conjugated diene unit, the non-conjugated olefin unit, and the aromatic vinyl unit. From the viewpoint of obtaining the desired effect, the content of other structural units is preferably 30% by mass or less of the whole multicomponent copolymer, more preferably 20% by mass or less, and even more preferably 10% by mass or less, and it is particularly preferable that they are not contained, that is, the content is 0% by mass.

[0022] The multicomponent copolymer is a multicomponent copolymer containing at least one kind of conjugated diene unit, one kind of non-conjugated olefin unit, and one kind of aromatic vinyl unit. From the viewpoint of obtaining favorable breaking characteristics, the multicomponent copolymer is preferably a polymer obtained by polymerizing at least one kind of conjugated diene compound, one kind of non-conjugated olefin compound, and one kind of aromatic vinyl compound as monomers. The multicomponent copolymer is more preferably a terpolymer consisting of only one type of conjugated diene unit, one type of non-conjugated olefin unit, and one type of aromatic vinyl unit, and even more preferably a terpolymer consisting of only 1,3-butadiene units, ethylene units, and styrene units. Here, the term "one type of conjugated diene unit" includes conjugated diene units having different bonding modes.

[0023] A multicomponent copolymer contains conjugated diene units, non-conjugated olefin units, and aromatic vinyl units, and one of its major characteristics is that the main chain is composed only of acyclic structures. If the main chain has a cyclic structure, the breaking properties (especially the breaking elongation) are reduced. In addition, NMR is used as a main measurement means to confirm whether the main chain of a multicomponent copolymer has a cyclic structure or not. Specifically, if a peak derived from a cyclic structure present in the main chain (for example, a peak appearing at 10 to 24 ppm for three-membered to five-membered rings) is not observed, it indicates that the main chain of the multicomponent copolymer is composed only of acyclic structures. Furthermore, as described below, the multicomponent copolymer can be synthesized in one reaction vessel, i.e., one-pot synthesis, and can be produced by a simplified process.

[0024] The multicomponent copolymer preferably has a polystyrene-equivalent weight average molecular weight (Mw) of 10,000 to 10,000,000, more preferably 100,000 to 9,000,000, and even more preferably 150,000 to 8,000,000. When the multicomponent copolymer has an Mw of 10,000 or more, the standard strength required for a golf ball material can be sufficiently ensured, and when the Mw is 10,000,000 or less, high workability can be maintained. The weight average molecular weight and molecular weight distribution described above are determined by gel permeation chromatography (GPC) using polystyrene as a standard substance.

[0025] The chain structure of the multicomponent copolymer is not particularly limited and can be appropriately selected according to the purpose. For example, when the conjugated diene unit is A, the non-conjugated olefin unit is B, and the aromatic vinyl unit is C, the multicomponent copolymer may be a block copolymer having a structure such as Ax-By-Cz (x, y, and z are integers of 1 or more), a random copolymer having a structure in which A, B, and C are randomly arranged, a tapered copolymer in which the random copolymer and the block copolymer are mixed, or an alternating copolymer having a structure such as (ABC)w (w is an integer of 1 or more). The multicomponent copolymer may also be a structure in which the conjugated diene unit, the non-conjugated olefin unit, and the aromatic vinyl unit are linearly linked (linear structure), or a structure in which at least one of the conjugated diene unit, the non-conjugated olefin unit, and the aromatic vinyl unit is linked by forming a branched chain (branched structure). In addition, when the multicomponent copolymer has a branched structure, the branched chain can also be two-component or multi-component (i.e., the branched chain can include at least two of the conjugated diene unit, the non-conjugated olefin unit, and the aromatic vinyl unit). Therefore, among multicomponent copolymers, multicomponent copolymers having a branched structure with two or more branched chains can be clearly distinguished from conventional graft copolymers in which the backbone chain and the side chains are formed of one type of unit that is different from each other.

[0026] The production method of the multicomponent copolymer, the polymerization process, the production conditions of the polymerization catalyst used, etc. can be those described in the specification of Japanese Patent No. 6780827. It is preferable that the multicomponent copolymer is polymerized by a gadolinium metallocene complex catalyst.

[0027] When the component (II) is an olefin-unsaturated carboxylic acid binary copolymer, the number of carbon atoms in the olefin is preferably 2 or more, and the upper limit is preferably 8 or less, and particularly preferably 6 or less. Examples of such olefins include ethylene, propylene, butene, pentene, hexene, heptene, and octene, and ethylene is particularly preferred. Examples of unsaturated carboxylic acids having 3 to 8 carbon atoms include acrylic acid, methacrylic acid, 3,3-dimethylacrylic acid, ethacrylic acid, maleic acid (anhydride), and fumaric acid, and acrylic acid and methacrylic acid are particularly preferred.

[0028] In addition, when the above-mentioned (II) component is an olefin-unsaturated carboxylic acid-unsaturated carboxylic acid ester terpolymer, the olefin and the unsaturated carboxylic acid can be the same as those in the above-mentioned olefin-unsaturated carboxylic acid binary copolymer. In addition, as the unsaturated carboxylic acid ester, for example, the lower alkyl ester of the above-mentioned unsaturated carboxylic acid can be preferably used, and examples thereof include methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, and butyl acrylate. In particular, butyl acrylate (n-butyl acrylate, isobutyl acrylate) is preferably used.

[0029] In the above component (II), an olefin-unsaturated carboxylic acid copolymer (binary copolymer) or its metal salt can be used in combination with an olefin-unsaturated carboxylic acid-unsaturated carboxylic acid ester copolymer (ternary copolymer) or its metal salt. That is, when a binary copolymer or its metal salt (a) is used in combination with a ternary copolymer or its metal salt (b), it is preferable to mix them in such a mass ratio that (a):(b)=0:100 to 80:20. If the amount of (a) is more than the above range, sufficient rebound resilience may not be obtained.

[0030] In addition, when a metal neutralized product is used as component (II), i.e., when an ionomer is used, the type and neutralization degree of the metal neutralized product are not particularly limited. Specific examples thereof include ethylene-methacrylic acid copolymer with 60 mol% Zn (degree of zinc neutralization), ethylene-methacrylic acid copolymer with 40 mol% Mg (degree of magnesium neutralization), and ethylene-methacrylic acid-isobutylene acrylate terpolymer with 40 mol% Mg (degree of magnesium neutralization).

[0031] Specific examples of the component (II) that can be used include commercially available products such as "Himilan" and "Nucrel" brand products (both manufactured by Dow Mitsui Polychemicals) and "Escol" brand products (manufactured by ExxonMobil Chemical).

[0032] The content of the above component (II) is not particularly limited, but the content of the component (II) relative to the total amount of the components (I) and (II) is preferably 5 to 95 mass%, and more preferably 20 to 80 mass%.

[0033] The golf ball material of the present invention may contain various additives as necessary, such as pigments, dispersants, antioxidants, light stabilizers, ultraviolet absorbers, and release agents.

[0034] The golf ball material of the present invention can be obtained by mixing the above-mentioned components using various kneading machines such as a kneading type (single screw or) twin screw extruder, a Banbury mixer, or a kneader.

[0035] The golf ball material of the invention preferably has a rebound resilience of at least 45%, and more preferably at least 49%, as measured according to JIS-K 6255. If the rebound resilience is too low, the initial velocity of the ball on approach shots can be reduced, but the flight distance on driver shots will be significantly reduced.

[0036] With regard to the material hardness, from the viewpoint of the spin characteristics and soft feel obtained as a golf ball, the Shore D hardness is preferably 25 or more, and more preferably 35 or more, and the upper limit is preferably 75 or less, more preferably 65 or less, and even more preferably 60 or less.

[0037] The golf ball material of the present invention can be used particularly as the cover material (intermediate layer and outermost layer) of a two-piece solid golf ball consisting of a core and a cover encasing the core, or a multi-piece solid golf ball consisting of one or more layers of a core and a multi-layer cover encasing the core.

[0038] The various components of a golf ball using the golf ball material of the present invention are described below.

[0039] The core can be formed using a known rubber material as the base material. Known base rubbers such as natural rubber or synthetic rubber can be used as the base rubber, and more specifically, it is recommended to mainly use polybutadiene, particularly cis-1,4-polybutadiene having at least 40% or more of a cis structure. Furthermore, in the base rubber, natural rubber, polyisoprene rubber, styrene butadiene rubber, etc. can be used in combination with the above-mentioned polybutadiene, if desired.

[0040] Polybutadiene can also be synthesized using metal catalysts such as rare earth element catalysts such as Nd catalysts, cobalt catalysts, and nickel catalysts.

[0041] The above base rubber may be blended with co-crosslinking agents such as unsaturated carboxylic acids and their metal salts, inorganic fillers such as zinc oxide, barium sulfate, calcium carbonate, and organic peroxides such as dicumyl peroxide and 1,1-bis(t-butylperoxy)cyclohexane, etc. Also, commercially available antioxidants and the like may be added as necessary.

[0042] The diameter of the core is appropriately selected depending on the structure of the ball and is not particularly limited, but is preferably at least 20 mm, more preferably at least 25 mm, and even more preferably at least 30 mm, with the upper limit being preferably no more than 41 mm, and more preferably no more than 40 mm.

[0043] An intermediate layer may be provided between the core and the outermost cover layer. In this case, the material hardness of the intermediate layer is not particularly limited, but may be 50 or more, preferably 55 or more, and more preferably 60 or more in Shore D hardness. The upper limit is also not particularly limited, but may be preferably 70 or less, and more preferably 65 or less.

[0044] There are no particular limitations on the thickness of the outermost layer of the cover, but it is preferably 0.3 mm or more, more preferably 0.4 mm or more, and even more preferably 0.5 mm or more, and the upper limit is preferably 1.2 mm or less, more preferably 1.0 mm or less, and even more preferably 0.8 mm or less.

[0045] A large number of dimples of one or more types may be formed on the surface of the cover. The surface of the cover may further be coated with various types of paint, and preferred examples of such paint include two-component curing urethane paints, particularly non-yellowing urethane paints, which must be able to withstand the harsh conditions of use of golf balls.

[0046] To obtain the cover, for example, a method can be adopted in which a single-layered or multi-layered core of two or more layers previously prepared according to the type of ball is placed in a mold, the mixture is heated, mixed, melted, and injection molded to cover the core with the desired cover. In this case, the cover can be manufactured under conditions that ensure excellent thermal stability, fluidity, and moldability, and the final golf ball has high resilience and a good hitting feel. In addition to the above, the cover can also be formed by, for example, previously forming a pair of hemispherical half cups from the cover material, wrapping the core in the half cups, and pressure molding at 120 to 170°C for 1 to 5 minutes. EXAMPLES

[0047] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0048] [Examples 1 to 7, Comparative Examples 1 to 8] A rubber composition containing polybutadiene as a main component, which is common to all the Examples and Comparative Examples shown in Table 1 below, was used to prepare a solid core having a diameter of 38.7 mm for each example by vulcanization at 152° C. for 19 minutes.

[0049] [Table 1]

[0050] The details of the core material are as follows. "Polybutadiene" manufactured by JSR Corporation, product name "BR51" "Zinc acrylate" manufactured by Nippon Shokubai Co., Ltd., product name "ZN-DA85S" "Organic peroxide" Dicumyl peroxide, NOF Corporation, product name "Percumyl D" "Anti-aging agent" manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Nocrac NS-6" "Zinc oxide" manufactured by Sakai Chemical Industry Co., Ltd., product name "Triple zinc oxide" "Pentachlorothiophenol zinc salt" manufactured by Wako Pure Chemical Industries, Ltd. "Zinc dimethacrylate" manufactured by Wako Pure Chemical Industries, Ltd. "Water" Pure water (manufactured by Seiki Pharmaceutical Co., Ltd.)

[0051] Formation of cover layer (middle layer and outermost layer) Next, the resin composition shown in Table 2 below is applied by injection molding to coat the periphery of the core obtained above, producing a sphere coated with a 1.2 mm thick intermediate layer having a Shore D hardness of 66 (intermediate layer-coated sphere).

[0052] [Table 2]

[0053] The details in the above table are as follows: "AM7318" Ionomer resin manufactured by Dow Mitsui Polychemicals "Himilan 1706" Ionomer resin manufactured by Dow Polychemicals "Trimethylolpropane" manufactured by Tokyo Chemical Industry Co., Ltd.

[0054] Next, the resin compositions shown in Tables 3 and 4 below were kneaded in a Labo Plastomill at 160°C for 30 minutes, and then the intermediate layer-coated spheres were coated with the resin compositions by injection molding to produce spheres (three-piece golf balls) coated with an outermost layer having a thickness of 0.8 mm. During this process, common dimples were formed on the cover surfaces of the examples and comparative examples, although not shown in the figures.

[0055] The materials in Tables 3 and 14 are as follows. "AM7318" Ionomer resin manufactured by Dow Mitsui Polychemicals "AN4319" "Nucrel" manufactured by Mitsui Dow Polychemicals "HPF2000" manufactured by The Dow Chemical Company "SEBS" is a product name of Asahi Kasei Corporation, "SOE S1606" "Multicomponent copolymer A" Details below "Multicomponent copolymer B" Details below

[0056] [Multicomponent copolymer A] Add 80 g of styrene and 600 mL of toluene to a thoroughly dried 1,000 mL pressure-resistant stainless steel reactor. In a glove box under a nitrogen atmosphere, 0.25 mmol of mono(bis(1,3-tert-butyldimethylsilyl)indenyl)bis(bis(dimethylsilyl)amide) gadolinium complex (1,3-[(t-Bu)Me2Si]2C9H5Gd[N(SiHMe2)2]2), 0.275 mmol of dimethylanilinium tetrakis(pentafluorophenyl)borate [Me2NHPhB(C6F5)4], and 1.1 mmol of diisobutylaluminum hydride are charged into a glass vessel, and 40 mL of toluene is added to prepare a catalyst solution. The catalyst solution is added to the pressure-resistant stainless steel reactor and heated to 70°C. Next, ethylene is charged into the pressure-resistant stainless steel reactor at a pressure of 1.5 MPa, and 80 mL of a toluene solution containing 20 g of 1,3-butadiene is further charged into the pressure-resistant stainless steel reactor over 8 hours, and copolymerization is carried out at 70° C. for a total of 8.5 hours. Next, 1 mL of a 5% by mass solution of 2,2'-methylene-bis(4-ethyl-6-t-butylphenol) (NS-5) in isopropanol is added to the pressure-resistant stainless steel reactor to stop the reaction. Next, the copolymer is separated using a large amount of methanol and vacuum dried at 50° C. to obtain copolymer A.

[0057] [Multicomponent copolymer B] Add 95 g of styrene and 400 mL of toluene to a thoroughly dried 1,000 mL pressure-resistant stainless steel reactor. In a glove box under nitrogen atmosphere, 0.17 mmol of mono(bis(1,3-tert-butyldimethylsilyl)indenyl)bis(bis(dimethylsilyl)amide) gadolinium complex (1,3-[(t-Bu)Me2Si]2C9H5Gd[N(SiHMe2)2]2), 0.187 mmol of dimethylanilinium tetrakis(pentafluorophenyl)borate [Me2NHPhB(C6F5)4], and 1.4 mmol of diisobutylaluminum hydride are charged into a glass vessel, and 40 mL of toluene is added to obtain a catalyst solution. The catalyst solution is added to the pressure-resistant stainless steel reactor and heated to 70°C. Next, ethylene is added to the pressure-resistant stainless steel reactor at a pressure of 1.5 MPa, and 150 mL of a toluene solution containing 27 g of 1,3-butadiene is added to the pressure-resistant stainless steel reactor over 30 minutes, and copolymerization is performed for 6 hours at 70° C. After that, 150 mL of a toluene solution containing 27 g of 1,3-butadiene is added to the pressure-resistant stainless steel reactor over 30 minutes, and copolymerization is performed for another hour at 70° C. Next, 1 mL of a 5% by mass solution of 2,2'-methylene-bis(4-ethyl-6-t-butylphenol) (NS-5) in isopropanol is added to the pressure-resistant stainless steel reactor to stop the reaction. Next, the copolymer is separated using a large amount of methanol and vacuum dried at 50° C. to obtain copolymer B.

[0058] For each of the "multicomponent copolymer A" and "multicomponent copolymer B," the contents (mass%) of butadiene, ethylene, and styrene are measured and evaluated by the following method. <Butadiene, ethylene, and styrene content> The contents of butadiene, ethylene, and styrene in each copolymer 1 The results are as follows: "Multicomponent copolymer A": Butadiene / ethylene / styrene = 14 / 70 / 16 (mass%) Weight average molecular weight (Mw) 273 x 10 3 "Multicomponent copolymer B": Butadiene / ethylene / styrene = 32 / 49 / 19 (mass%) Weight average molecular weight (Mw) 375 x 10 3

[0059] The material hardness and rebound resilience of the cover of the above three-piece golf ball were measured as follows, with the results shown in Tables 3 and 4 below.

[0060] Cover material hardness (Shore D hardness) The resin material for the cover was molded into a 2 mm thick sheet and left for at least two weeks, after which the Shore D hardness was measured according to the ASTM D2240-95 standard.

[0061] Rebound elasticity The resin material was formed into a 2 mm thick sheet using a press, stacked to a thickness of 4 mm, and the temperature was adjusted to 23±1°C. The resilience was then measured using a Tripson type resilience device based on JIS-K 6255 (2013) (note that the drop angle specified in the JIS-K 6255 standard was adjusted to 30 degrees to measure the resilience modulus above).

[0062] [Table 3]

[0063] [Table 4]

[0064] Fig. 1 is a graph showing the relationship between the material hardness and the rebound resilience of the covers in Examples 1 to 5 and Comparative Examples 1 to 5 in Table 3. Fig. 2 is a graph showing the relationship between the material hardness and the rebound resilience of the covers in Examples 6 and 7 and Comparative Examples 6 to 8 in Table 4. 1 and 2, when the material hardness is the same between the Example and the Comparative Example, the Example has a higher resilience modulus than the Comparative Example.

Claims

1. The following components (I) and (II) (I) a multicomponent copolymer having a conjugated diene unit, a non-conjugated olefin unit, and an aromatic vinyl unit; and (II) A binary copolymer of an olefin and an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms, and / or a ternary copolymer of an olefin and an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms and an α,β-unsaturated carboxylic acid ester thereof, or a metal-neutralized product thereof the conjugated diene units include butadiene units, the non-conjugated olefin units include units selected from the group consisting of ethylene units, propylene units and 1-butene units, the aromatic vinyl units include styrene units, and the content of the conjugated diene units in the multi-component copolymer is 10 to 80% by mass.

2. 2. The golf ball material according to claim 1, wherein the content of the non-conjugated olefin units in the multicomponent copolymer which is component (I) is 20 to 90% by weight.

3. 3. The golf ball material according to claim 1, wherein the content of the aromatic vinyl units in the multicomponent copolymer which is component (I) is 3 to 30% by weight.

4. 4. The golf ball material of claim 1, wherein the non-conjugated olefin units are ethylene units.

5. 5. The golf ball material according to claim 1, wherein the multicomponent copolymer of component (I) is a copolymer polymerized with a gadolinium metallocene complex catalyst.

6. 6. The golf ball material according to claim 1, wherein the content of component (II) based on the total amount of components (I) and (II) is 5 to 95% by mass.

7. 7. The golf ball material of claim 1, wherein the material has a Shore D hardness of 25 to 65.

8. 8. The golf ball material according to claim 1, which is used as a cover material for a golf ball.

9. A golf ball having a core consisting of one or more layers and a cover consisting of one or more layers encasing the core, wherein at least one layer of the cover is formed from the golf ball material according to any one of claims 1 to 8.